El gobierno de la carretera - Ilizarbe, Carmen (Pontificia Universidad Católica del Perú, 2025)
Clashes over extractive projects in Peru between the State and peasant communities have increased and expanded throughout the country during the 21st century, despite policies promoting dialogue and negotiation encouraged by various governments. Rather, the use of exceptional regimes, in the form of declaration of state of emergency to address protests, has become normalized, and in some cases, this normalization has allowed for the establishment of authoritarian enclaves. Why are authoritarian enclaves established? How are they governed? What mechanisms make authoritarian government possible? This article studies, analyzing the history of the approval and construction of a mining corridor, how and why the Peruvian State instituted an authoritarian enclave in the surroundings of the Las Bambas mining project, between 2015 and 2020. The analysis is based on three analytical inputs: 1) the reconstruction of the legal-juridical process that institutionalizes the authoritarian enclave, 2) a characterization of the type of government and governmental mechanisms used in this geopolitical space, and 3) an ethnographic account of the dynamics of circulation and immobility that are imposed in the corridor, and reveal the functioning of the authoritarian enclave.

Los enfrentamientos por proyectos extractivos en el Perú entre el Estado y comunidades campesinas se han incrementado y expandido por el territorio nacional durante el siglo XXI, a pesar de las políticas de promoción del diálogo y la negociación impulsadas por distintos gobiernos. Se ha normalizado el recurso al régimen de excepción, en la modalidad de la declaratoria de estado de emergencia, para enfrentar las protestas, y en algunos casos esa normalización ha permitido la institución de enclaves autoritarios. ¿Por qué se instituyen enclaves autoritarios? ¿Cómo se gobiernan? ¿Qué mecanismos hacen posible el gobierno autoritario? Este artículo estudia, a través de la historia de la aprobación y construcción de un corredor minero, cómo y por qué el Estado peruano instituyó un enclave autoritario en los alrededores de la mina Las Bambas entre los años 2015 y 2020. El análisis se apoya en tres entradas analíticas: 1) la reconstrucción del proceso jurídico-legal que da origen institucional al enclave autoritario, 2) el análisis del sistema de gobierno en este ámbito geopolítico y de los procesos y procedimientos que lo hacen posible, y 3) un recorrido etnográfico por la carretera para tomarle el pulso a las dinámicas de circulación e inmovilismo que allí se imponen y revelan el funcionamiento del enclave autoritario.
The Highway’s Government
Keywords: Regime of exception; Neoliberalism; Authoritarianism; Extractivism; Peru; Régimen de excepción; Neoliberalismo; Autoritarismo; Extractivismo; Perú; https://purl.org/pe-repo/ocde/ford#5.04.03